PASANG SURUT GERAKAN FEMINISME - Saidul Amin (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
The FeminismMovement has played on important role in spreading the spirit of struggle for woman’s right and freedom in the history of human civilization. However this movement also caused negative aspects on social life. That is the main idea of trying to put forward in this article, the fall and rise of feminism movement from the beginning unti lthe contemporary age.